How young is too young to start training? - Myer, G. D.; Lloyd, R. S.; Brent, J. L.; Faigenbaum, A. D. (ACSM's Health & Fitness Journal, 2013)
LEARNING OBJECTIVES •To introduce an integrative neuromuscular training model that can be used to enhance the health, fitness, and wellness of all children and adolescents. •To understand the potential benefits associated with strength and conditioning programs implemented with youth to reduce injury risk and enhance motor skill development that will support a physically active lifestyle. •To comprehend the concept of "training age" and the implications associated with systematic training beginning during early childhood.